How markets really work : a quantitative guide to stock market behavior - Connors, Laurence A.; Alvarez, Cesar, 1967- (Hoboken, New Jersey : John Wiley & Sons, Inc., 2012)
For years, traders and investors have been using unproven assumptions about popular patterns such as breakouts, momentum, new highs, new lows, market breadth, put/call ratios and more without knowing if there is a statistical edge.Common wisdom holds that the stock markets are ever changing. But, as it turns out, common wisdom can be wrong. Offering a comprehensive look back at the way the markets have acted over the last two decades, How Markets Really Work: A Quantitative Guide to Stock Market Behavior, Second Edition shows that nothing has changed, that the markets behave the same way today.
How Markets Really Work: A Quantitative Guide to Stock Market Behavior; Contents; Disclaimer; Table Explanation; Acknowledgments; Chapter 1: Market Edges; Chapter 2: Short-Term Highs and Short-Term Lows; Chapter 3: Higher Highs and Lower Lows; Chapter 4: Up Days in a Row versus Down Days in a Row; Chapter 5: Market Breadth; Chapter 6: Volume; Chapter 7: Large Moves; Chapter 8: New 52-Week Highs, New 52-Week Lows; Chapter 9: Put/Call Ratio; Chapter 10: Volatility Index (VIX); Chapter 11: The Two-Period RSI Indicator; Chapter 12: Historical Volatility.
Includes index.
Print version record and CIP data provided by publisher.
Keywords: Stock exchanges -- United States; Investment analysis -- United States; Stocks -- United States; Business; BUSINESS & ECONOMICS -- Finance; Stock exchanges; United States; Electronic books; Electronic books